Republic of Moldova : Fourth and Fifth Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements, Completion of the Inflation Consultation, and Request for Extension of the Arrangements and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Republic of Moldova's Fourth and Fifth Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements, Completion of the Inflation Consultation, and Request for Extension of the Arrangements and Rephasing of Access. The Moldovan authorities have taken decisive corrective measures to bring the Fund supported program back on track and to achieve its objectives of ensuring macroeconomic stability and advancing reforms. Going forward, it is critical that the authorities continue to pursue prudent policies and structural reforms aimed at strengthening the financial sector, maintaining fiscal sustainability, and creating space for social and infrastructure spending. Policies remain focused on cleansing the financial sector, ensuring growth friendly fiscal policy, and enhancing transparency in the energy sector. The authorities are committed to completing the rehabilitation of the banking system, addressing vulnerabilities in the non-bank sector, promoting predictable energy tariff setting, and maintaining fiscal sustainability to preserve space for social and infrastructure spending.